Clinical Characteristic and Microbiological Findings in Bacterial Corneal Ulcer at A Private Eye Clinic in Jakarta - Nelandriani Yudapratiwi; Rifna Lutfiamida; Yulinda Indarnila Soemiatno (Majalah Oftalmologi Indonesia, 2016)
Background: Corneal ulcer is a major cause of blindness in developing countries causing prolongedmorbidity, loss of vision, and often loss of eyes. Corneal ulcer is an ocular emergency that requiresprompt and appropriate management to ensure the best visual outcome for the pattern of bacterialcorneal ulcers at a private eye clinic in Jakarta, and to test these bacteria against routinely used ocularantibiotics in order to formulate new guidelines for therapy.Methods: This was a descriptive study. All patients treated for bacterial corneal ulcers who agreed toparticipate in this study were prospectively followed. Clinical features (age, risk factors, visual acuity)and response to therapy were observed. Bacteriological profile was determined and the antibioticsusceptibility tests were done.Results: Fifteen consecutive patients with bacterial corneal ulcer (median age 39, SD 19.1) wereprospectively enrolled from September 2012 to November 2014. The predisposing factors weretrauma (40%), contact lens (33.3%), eyelid abnormalities (13.3%), and keratopathies (13.3%). Growthfrom culture was found in five patients and all of them had results of Pseudomonas sp. The isolatedPseudomonas sp was susceptible to gentamicin, levofloxacin, tobramycin, and ofloxacin. Eighty percentof patients had improved conditions with improved visual outcome.Conclusion: In this series, ocular trauma and contact lens wear were the most common predisposingfactor. Pseudomonas sp was the only microorganism isolated from the culture. The isolated bacteriawere sensitive to gentamicin, tobramycin, ofloxacin, and levofloxacin.Â Keywords: bacterial corneal ulcer, culture, corneal trauma, contact lens, antibiotic susceptibility test